Employment outcomes research in vocational rehabilitation: implications for rehabilitation counselor (RC) training. - Fraser RT; Vandergoot D; Thomas D; Wagner CC (Journal of Vocational Rehabilitation, 2004)
This paper reviews salient categories of rehabilitation programs' employment outcomes research, as recently presented by the authors at the May 2002 'Bridging Gaps' conference, sponsored by the National Institute of Disability and Rehabilitation Research (NIDRR) and the Office of Special Education and Rehabilitation Services (OSERS), US Department of Education and several co-sponsors (e.g., the American Psychological Association/Rehabilitation Psychology, Division 22, etc.). The purpose of this paper is to review these findings and draw the most relevant implications for rehabilitation counselor training programs' curricula. The paper begins with a review of the contextual changes affecting vocational rehabilitation (VR) services delivery today and then presents employment outcomes research findings as related to the vocational rehabilitation participant, the rehabilitation counselor in the placement process, and the actual services provided. Implications for rehabilitation counseling curricula are presented not only in relation to job placement coursework, but also coursework relating to counseling strategies, vocational assessment, and medical aspects of disability. Modifications to coursework in the above areas (and potentially others) should have impact in preparing more of an 'employment outcomes skilled and oriented' RC program graduate.